PENGARUH MANAJEMEN PESANTREN DAN KINERJA PEMBINA PESANTREN TERHADAP KEDISIPLINAN SANTRI - Ahmad Zakir Haidar; Suwandi; Mufaizin Mufaizin (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
The world of education today must be treated and managed professionally, because of the increasingly intense competition, educational institutions will be abandoned by consumers or society if managed soberly. Islamic boarding schools are non-profit educational institutions engaged in educational services. With increasingly fierce competition, like it or not, every school must carry out good management in order to provide the best service, because if this is not the case, then consumers or the public will easily look for other institutions that are more profitable and promising. So the management with the best management is needed. This study has the objectives, (1) To determine the effect of Islamic boarding school management on the discipline of students at Pondok Pesantren Al Aqobah 4 Jombang. (2) To determine the effect of the performance of the pesantren supervisor on the discipline of students at the Al Aqobah Islamic Boarding School 4 Jombang. (3) To find out the influence of pesantren management and the performance of the pesantren supervisors on the discipline of students at Al Aqobah Islamic Boarding School 4 Jombang. This study uses a quantitative approach, with the type of research ex post facto. The sample in this study were 186 students as respondents, using probability sampling using simple random sampling technique. Data acquisition was carried out using a distributed questionnaire in the form of 40 (forty) statement items. And using data analysis techniques with multiple linear regression tests. The results of this study indicate that. (1) There is a partial influence between the management of the pesantren on the discipline of the students. This is evidenced by the results of the hypothesis test finding a significance value of T = 0,022 < 0,05, then Ho is rejected and Ha is accepted. (2) There is no partial influence between the performance of the pesantren supervisors on the discipline of the students. This is evidenced by the results of the hypothesis test finding a significance value of T = 0,318 > 0,05, then Ho is accepted and Ha is rejected. (3)There is a  simultaneous influence between the management of the pesantren and the performance of the pesantren supervisors on the discipline of the santri. This is evidenced by the results of the hypothesis test finding a significance value of F = 0.51 > 0.05, then Ho is rejected and Ha is.accepted